COVID-19 Epidemic in Argentina: Worsening of Behavioral Symptoms in Elderly Subjects With Dementia Living in the Community - Cohen, Gabriela; Russo, María Julieta; Campos, Jorge A.; Allegri, Ricardo F. (Frontiers in psychiatry, 2020)
In Argentina, the quality of care that elderly subjects with dementia living in the community received has been deeply affected by COVID-19 epidemic. Our objective was to study to what extend mandatory quarantine imposed due to COVID-19 had affected behavioral symptoms in subjects with dementia after the first 8 weeks of quarantine. We invited family members to participate in a questionnaire survey. The sample consisted of family caregivers (n = 119) of persons with AD or related dementia living at home. We designed a visual analog scale to test the level of the burden of care of family members. Items inquired in the survey included type and setting (home or day care center) of rehabilitation services (physical/occupational/cognitive rehabilitation) and change in psychotropic medication and in behavioral symptoms that subjects with dementia experienced before and during the epidemic. Characteristics of people with dementia and their caregivers were analyzed with descriptive statistics using the chi-square tests, p < 0.01 was considered significant. Results: The sample included older adults with dementia. Mean age: 81.16 (±7.03), 35% of the subjects had more than 85 years of age. Diagnosess were 67% Alzheimer´s dementia and 26% mixed Alzheimer´s disease (AD). Stages were 34.5% mild cases, 32% intermediate stage, and 33% severe cases as per Clinical dementia Rating score. In 67% of the sample, a family member was the main caregiver. Important findings were increased anxiety (43% of the sample), insomnia (28% of the subjects), depression (29%), worsening gait disturbance (41%), and increase use of psychotropics to control behavioral symptoms. When we compared the frequency of behavioral symptoms within each dementia group category, we found that anxiety, depression, and insomnia were more prevalent in subjects with mild dementia compared to subjects with severe dementia. We analyzed the type and pattern of use of rehabilitation services before and during the isolation period, and we observed that, as a rule, rehabilitation services had been discontinued in most subjects due to the quarantine. We concluded from our analysis that during COVID-19 epidemic there was a deterioration of behavioral symptoms in our population of elderly dementia subjects living in the community. Perhaps, our findings are related to a combination of social isolation, lack of outpatient rehabilitation services, and increased stress of family caregivers. It is necessary to develop a plan of action to help dementia subjects deal with the increased stress that this epidemic imposed on them.In Argentina, the quality of care that elderly subjects with dementia living in the community received has been deeply affected by COVID-19 epidemic. Our objective was to study to what extend mandatory quarantine imposed due to COVID-19 had affected behavioral symptoms in subjects with dementia after the first 8 weeks of quarantine. We invited family members to participate in a questionnaire survey. The sample consisted of family caregivers (n = 119) of persons with AD or related dementia living at home. We designed a visual analog scale to test the level of the burden of care of family members. Items inquired in the survey included type and setting (home or day care center) of rehabilitation services (physical/occupational/cognitive rehabilitation) and change in psychotropic medication and in behavioral symptoms that subjects with dementia experienced before and during the epidemic. Characteristics of people with dementia and their caregivers were analyzed with descriptive statistics using the chi-square tests, p < 0.01 was considered significant. Results: The sample included older adults with dementia. Mean age: 81.16 (±7.03), 35% of the subjects had more than 85 years of age. Diagnosess were 67% Alzheimer´s dementia and 26% mixed Alzheimer´s disease (AD). Stages were 34.5% mild cases, 32% intermediate stage, and 33% severe cases as per Clinical dementia Rating score. In 67% of the sample, a family member was the main caregiver. Important findings were increased anxiety (43% of the sample), insomnia (28% of the subjects), depression (29%), worsening gait disturbance (41%), and increase use of psychotropics to control behavioral symptoms. When we compared the frequency of behavioral symptoms within each dementia group category, we found that anxiety, depression, and insomnia were more prevalent in subjects with mild dementia compared to subjects with severe dementia. We analyzed the type and pattern of use of rehabilitation services before and during the isolation period, and we observed that, as a rule, rehabilitation services had been discontinued in most subjects due to the quarantine. We concluded from our analysis that during COVID-19 epidemic there was a deterioration of behavioral symptoms in our population of elderly dementia subjects living in the community. Perhaps, our findings are related to a combination of social isolation, lack of outpatient rehabilitation services, and increased stress of family caregivers. It is necessary to develop a plan of action to help dementia subjects deal with the increased stress that this epidemic imposed on them.